PERAN EKSTRAKULIKULER PENCAK SILAT DALAM MENANAMKAN KARAKTER DISIPLIN SISWA DI SDS AL IRSYAD AL ISLAMIYYAH - Noviyanti, Nina Gustina; Abdul Halim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to understand how extracurricular pencak silat activities can shape the discipline of students at Al-Irsyad Al-Islamiyyah Elementary School. Discipline is an important character trait that needs to be instilled from an early age. Pencak silat, as a traditional martial art, trains not only the physical but also the mental and spiritual, which are believed to influence character formation. The research method used was descriptive qualitative, where data were collected through direct observation of student behavior during pencak silat training, as well as interviews with teachers/coaches and several students. The researcher observed five students as the primary sample to observe changes and development in their discipline. The results showed that extracurricular pencak silat played a very effective role in instilling discipline in students. Aspects of discipline such as punctuality, adherence to instructions, neatness of dress (uniform), and a sense of responsibility were observed to improve in the students. Although there was slight variation in the level of focus and enthusiasm among some students, in general, the disciplinary values ​​taught in pencak silat were well internalized and led to positive changes in their behavior. Thus, it can be concluded that the pencak silat extracurricular is not only a means of physical development, but is also a strong and effective medium for forming the holistic character of student discipline at SDS Al-Irsyad Al-Islamiyyah.